Het Sociaal Historisch Centrum voor Limburg: zijn missie en zijn collecties - Hovens, Frank (Studies over de sociaaleconomische geschiedenis van Limburg, 2021)
Sociaal Historisch Centrum voor Limburg (SHCL), the Centre for the Social History of Limburg, was founded in 1949. Its primary objective was the collection and conservation of ‘historical sources regarding social life in the province of Limburg’. This collection of archives, documentation, literature and imagery was meant to constitute the basis for scientific historical research. Over the past 76 years, those two, collection and research, have been important pillars of SHCL’s activities. In more recent times, public outreach has become another major task. In the early years, SHCL’s policy was predicated on the idea of pursuing social cohesion along Catholic principles. Later, with the waning of Catholicism in Limburg, this ambition faded away. From the beginning SHCL wanted to produce research that fulfilled academic criteria. The establishment of Maastricht University (UM) in 1976 enhanced this aspiration even further. The relationship between SHCL and UM is reinforced by a special research chair, in comparative regional history of the province of Limburg and adjacent regions, held by SHCL’s director at the university. The gradual growth of the archival collection and library mirrors SHCL’s mission and institutional history. The centre has a long tradition of studying the social history of Limburg and its inhabitants, by relying on extensive archives related to agriculture, mining and other industries, and civil society. More recently SHCL has widened this focus by collecting sources on the social history of the landscape as well. As to its overall mission, SHCL is exploring new ways to engage with today’s rapidly changing society, and the interests of the people living in it.